2010
DOI: 10.1007/s00542-010-1037-5
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent fracture toughness of glass frit bonding layers

Abstract: Glass frit bonding is an important technology for the hermetical encapsulation of microsensors. During manifactiring processes and in application the bonding layer is repeatedly exposed to temperature changes. Therefore a meaningful stability assessment must consider possible temperature dependent fracture toughness parameters. This work shows that the influence of temperature changes on the fracture toughness depends on whether the bonding layer is subjected to externally pure tensile or combined tensile and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Using rather high amounts of plasticizer in the paste allows it, in the dried state, to conform to the seal under the influence of the weight, reducing the degree of required flow upon firing. Long sealing time at high temperature (> 10 minutes) and using weights improve glass flow, but can have the adverse consequence of deforming the glass substrates and/or breaking the carrier [20]. Here, the best results were obtained by sealing the carrier at 725°C for 20 minutes with a weight of 80 grams; no cracks were observed in the sealing glass layer as verified by the dye penetration test, as shown in Figure 6.…”
Section: Characterizationmentioning
confidence: 70%
“…Using rather high amounts of plasticizer in the paste allows it, in the dried state, to conform to the seal under the influence of the weight, reducing the degree of required flow upon firing. Long sealing time at high temperature (> 10 minutes) and using weights improve glass flow, but can have the adverse consequence of deforming the glass substrates and/or breaking the carrier [20]. Here, the best results were obtained by sealing the carrier at 725°C for 20 minutes with a weight of 80 grams; no cracks were observed in the sealing glass layer as verified by the dye penetration test, as shown in Figure 6.…”
Section: Characterizationmentioning
confidence: 70%
“…5.2 with the geometric function for 2c/a = 2 and 32 gives the values shown in Table 5.4. The lower value of K Ic for ZBLAN as compared to common amorphous silica glass is expected based on the literature review [Anstis, 1981;Nötzolda, 2010] and common perception of the fragile nature of ZBLAN fibers.…”
Section: Fracture Mechanics Analysesmentioning
confidence: 99%
“…They reported a coefficient of variation greater than 10% is common even in fibers with identical chemical/material composition; the probability distribution function of K Ic values of soda-lime glass was reported to be in the range of 0.5 to 0.9 MPa m 1/2 . Nötzolda et al, (2010) investigated the effect of residual stresses on fracture toughness in fritt-bonded glass plates. Their study showed that the effect of residual stress on fracture toughness depends on the nature of fracture (pure tensile vs. mixed mode).…”
Section: Effect Of Micro-crystals On Fiber Fracturementioning
confidence: 99%
“…Nötzold et al (59) have reported their experiments of the temperaturedependent fracture toughness parameters of the glass frit bonding used in microsensors. These parameters include material's resistance against crack propagation, the stress situation in a micropackage, and the long-term strength behavior.…”
Section: Glass Frit Bondingmentioning
confidence: 99%